2007
DOI: 10.1007/s10577-007-1168-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and intergenomic homology of B-genome chromosomes in trigenomic combinations of the cultivated Brassica species revealed by GISH analysis

Abstract: Intragenomic chromosome homology in the B genome of Brassica nigra and their homoeology with the chromosomes of the A-genome of B. rapa and C-genome of B. oleracea was investigated in triploids (ABC, n = 27) of different origins obtained following hybridizations between natural B. napus (AACC, 2n = 38) x B. nigra (BB, 2n = 16) [AC.B], synthetic B. napus x B. nigra [A.C.B] and B. carinata (BBCC, 2n = 34) x B. rapa (AA, 2n = 20) [BC.A]. A relatively high percentage of pollen mother cells (PMCs) with at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 77 publications
8
33
1
Order By: Relevance
“…According to the relative values of π and θ per bp, the B genome in B. juncea retained a higher level of variation (0.192, 0.0261) than the A genome (0.0092, 0.0158). This result reinforced the data presented by Song et al (2009) and Ge and Li (2007), which indicated that after the occurrence of polyploidy in mustard, the A and B genomes showed a different degree of variation and larger genetic variation within the B genome. The decreased variation in the A genome may be due to artificial selection, as evidenced by Fu and Li's D, Fu and Li's F, HKA test, and misalignment analysis.…”
Section: Sequence Polymorphism Of the Chs Gene In Chinese Mustardsupporting
confidence: 91%
“…According to the relative values of π and θ per bp, the B genome in B. juncea retained a higher level of variation (0.192, 0.0261) than the A genome (0.0092, 0.0158). This result reinforced the data presented by Song et al (2009) and Ge and Li (2007), which indicated that after the occurrence of polyploidy in mustard, the A and B genomes showed a different degree of variation and larger genetic variation within the B genome. The decreased variation in the A genome may be due to artificial selection, as evidenced by Fu and Li's D, Fu and Li's F, HKA test, and misalignment analysis.…”
Section: Sequence Polymorphism Of the Chs Gene In Chinese Mustardsupporting
confidence: 91%
“…Adding to the confusion, different researchers used separate systems of chromosome nomenclature. Finally, the use of genomic in situ hybridization (GISH) to distinguish the progenitor diploid A and C progenitor genomes failed in allopolyploid B. napus (Snowdon et al 1997), although GISH has allowed the visualization of the B diploid genome in allopolyploid B. juncea (Snowdon et al 1997;Maluszynska and Hasterok 2005) and in ABC trigenomic Brassica hybrids (Ge and Li 2007). GISH has also distinguished Brassica chromosomes from separate species in intergeneric hybrids of Brassica crossed to Lesquerella, Orychrophragmus, Raphanus, and Isatis (Sharzhinskaya et al 1998;Hua et al 2006;Liu and Li 2007;Du et al 2008;Tu et al 2008).…”
mentioning
confidence: 99%
“…Maluszynska and Hasterok (2005) combined a GISH analysis of B. juncea with FISH using labeled 5S rDNA and 45S rDNA probes to discriminate several chromosomes within each genome. GISH was also used in the analysis of the behavior of B genome chromosomes in the trigenomic hybrids ABC (Ge and Li 2007). However, an attempt to clearly discriminate the A genome from the C genome in B. napus by GISH was unsuccessful (Snowdon et al 1997).…”
mentioning
confidence: 99%